PERBANDINGAN PERLINDUNGAN PENCARI SUAKA DAN PENGUNGSI DI INDONESIA DAN NEGARA LAIN BERDASARKAN HAK ASASI MANUSIA: Comparison Of The Protection Of Asylum Seekers And Refugees In Indonesia And Other Countries Based On Human Rights - Nuril Firdausiah; Fona Kartika Listiyapuji (UIN Kiai Haji Achmad Siddiq Jember, 2023)
In principle, everyone has the right to move from one place to another, including leaving their own country and returning to their country. The problem of refugees is a quite complicated problem facing the world community today. In fact, everyone is guaranteed the right to seek and obtain asylum in another country to protect themselves from persecution. One form of population movement is displacement, both across countries and within the country's territory (Internal Displaced Persons). Displacement is a form of population movement that has different characteristics from other population movements, so it influences the protection mechanisms applied to them. In general, refugees are carried out because of the oppression of human rights in their country. Violations of human rights against an ethnic group by the country of origin force victims to flee to other countries to obtain protection so that both transit countries and destination countries that have not or have ratified the 1951 Convention must apply the principle of non-refoulement. Refugees are usually not provided with travel documents, so many experience abuse in their countries of origin, transit countries and destination countries. Each country is responsible for protecting refugees in their territory. To protect the rights and welfare of refugees, there is a special organization mandated by the United Nations (